Personalized presentations from community assets - Guimarães, Rodrigo Laiola; Cesar, Pablo; Bulterman, Dick (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Creating compelling multimedia productions is a non-trivial problem. The problem is compounded when authors want to integrate community media assets: media fragments contributed by a potentially wide and anonymous recording community. In this paper, we report on a hybrid authoring approach that provides mixed support for automated creation and manual enhancement of personalized multimedia presentations. We target small-scale events (such as a high school music concert), where lightly annotated media assets are provided. Our assumption is that enthusiastic, but less experienced, editors (e.g., parents and family members) will want to highlight personal aspects of each event: a particular child, a particular instrument or a particular solo. This places a requirement on a system that helps users to select appropriate content of personal interest, and that helps building compelling presentations with minimum user effort. Based on a 4-years user-centered evaluation process, this paper provides useful insights into how a multimedia authoring system should be designed and architected for helping users in creating personalized video stories they care about.